CONTEMPORARY FATWA AGAINST ISTINBAT APPROACH ISSUES OF CURRENT JURISPRUDENCE-ORIENTED SCIENCE AND TECHNOLOGY - Dr Mohammad Azam Hussain; Prof. Madya Dr Alias Azhar (Journal of Islamic, Social, Economics and Development, 2016)
The science and technology dynamics (S & T) have affected the change of Islamic law and the legal authority that also opens the door for legal review. Fatwa istinbat in the framework of contemporary ijtihad is very important in order to provide clear and realistic legal answers to current conditions. To form the foundation of the concept and the theory of this study, reference has been made to literary materials in library savings, important and official documents such as minutes of meetings, research reports, statistics, official documents Volume: 1 Issue: 2 [December, 2016] pp.01-07] Journal of Islamic, Social, Economics and Development eISSN: 0128-1755 Journal homepage: www.jised.com2 of the Department of Islamic Development Malaysia and the Mufti departments. The concepts and definitions of fatwa and the close relationship between ijtihad and fatwa serve as the basis of the discussion theory of this article. Fatwa changes occur based on time changes, places, conditions and 'implications of scientific and technological developments. The basic needs that need to be done to implement the Islamic law as a whole is the need to conduct the istiwabat fatwa in the framework of contemporary ijtihad. This requirement is aimed at becoming a progressive Islamic law and able to deal with new legal issues, thereby being practiced at all times and places.